Uji Model Fisik Bangunan Pelimpah Bendungan Saka Gilas Dengan Skala 1:50 - Rahmah Dara Lufira; Muhammad Amar Sajali; Suwanto Marsudi; Very Dermawan (Fakultas Teknik, Universitas Brawijaya, 2019)
The physical hydraulic model carried out in the laboratory is intended to determine the hydraulic behavior of the flow in hydraulic structures. The aim of Hydraulic model test of Sakagilas Dam spillway is to determine the flow profile that occurs in spillway system, including flow depth, velocity, water flow pressure, and Froude numbers. Also to find out the hydraulic performance of side spillway design, transition channel, chute way channel, energy dissipator, and escape channel. Investigation of water flow pressure in the spillway system (side channel spillway, transition channel, and especially chute way channel) was measured and analyzed to determine the condition of structure safety against cavitation and vibration flow.The spillway of Saka Gilas Dam is a side channel spillway (Fixed+Gated) with an Ogee spillway. The shape of the side spillway is circular quarter circle (45â°). Preliminary observations on the physical model test are carried out under the condition of Original Design, which if there is a poor flow hydraulic behavior, design modifications will be made. The design modification is intended to get the best flow hydraulic behavior, according to the standard design criteria for the side channel spillway system.